Respuestas
Respuesta dada por:
3
a + b = 55
a - b = 9
Por método de sustitución=
a + b = 55
a = 55 - b
reemplazas en la segunda ecuación=
a - b = 9
55 - b - b = 9
55 - 2b = 9
-2b = 9 - 55
-2b = -46
b = -46/-2
b = 23
a = 55 - b
a = 55 - 23
a = 32
a - b = 9
Por método de sustitución=
a + b = 55
a = 55 - b
reemplazas en la segunda ecuación=
a - b = 9
55 - b - b = 9
55 - 2b = 9
-2b = 9 - 55
-2b = -46
b = -46/-2
b = 23
a = 55 - b
a = 55 - 23
a = 32
janetespinoza12:
Gracias
Respuesta dada por:
2
55-9=46
46+9=55
osea la respuesta seria 46
46+9=55
osea la respuesta seria 46
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años